2018
DOI: 10.3390/su10082937
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experimental Laws for the Radon Exhalation of Similar Uranium Samples with Low-Frequency Vibrations

Abstract: Abstract:It is the fact that there are lots of hazard incidents in underground uranium mines caused by radon but in-suit uranium samples were difficult to collect. Based on closed chamber method, three similar samples in different sealed ways were made in a laboratory with different material rations, namely uranium tailings, quartz sand, cement, iron powder and silicon powder to measure the radon concentrations with and without low-frequency vibrations, which was used by the experimental device for low-frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The frequency of the debris flows is lower than 50 Hz, but after the front passed, the frequency is between 50 and 100 Hz. In these frequency ranges there is an increase in radon emanation and exhalation according to Cai et al (2018) and Cai et al (2019). These authors confirmed that one of the main sources of ground vibration caused by debris flows is the interaction of rocks or boulders with the channel bed.…”
Section: Rock and Debris Avalanches Due To Flooding Of Rivers During ...mentioning
confidence: 60%
See 1 more Smart Citation
“…The frequency of the debris flows is lower than 50 Hz, but after the front passed, the frequency is between 50 and 100 Hz. In these frequency ranges there is an increase in radon emanation and exhalation according to Cai et al (2018) and Cai et al (2019). These authors confirmed that one of the main sources of ground vibration caused by debris flows is the interaction of rocks or boulders with the channel bed.…”
Section: Rock and Debris Avalanches Due To Flooding Of Rivers During ...mentioning
confidence: 60%
“…The author considers the increased delivery of radon from the subsoil due to the enhanced upward diffusion. Cai et al (2018) and Cai et al (2019) studied the influence of low-frequency vibrations on the radon exhalation from uranium samples. The results showed that the radon exhalation increased with the rising vibration frequency until frequencies of about 50 to 70 Hz, but fell slowly after reaching the peak.…”
Section: Rock and Debris Avalanches Due To Flooding Of Rivers During ...mentioning
confidence: 99%
“…The appropriate blasting method should be selected based on the burial depth of the deposit [129]. For shallow deposits, either drilling-blasting [130] or chamber-blasting [131] methods can be employed. Usually, drilling blasting is preferable for shallow-buried thick deposits due to its more pronounced cost-effectiveness [132].…”
Section: Permeability Modification Technique For In Situ Leachingmentioning
confidence: 99%
“…Similar material simulating geotechnical mechanical properties must have the basic characteristics of high gravity, low strength, low deformation modulus, and variable internal friction angle. Materials that meet these requirements do not exist in nature and must be combined 2 of 15 manually [6,7]. In sum, selection and proportioning of similar materials play a decisive role in the physical similarity simulation test [8,9].…”
Section: Introductionmentioning
confidence: 99%